2003
DOI: 10.1080/03008200390223927
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of MMP-2, MMP-9, TIMP-1, and TIMP-2 in the Forming Rat Incisor

Abstract: Western blots analyses and gelatin zymography established the presence of matrix metalloproteinase (MMP)-2 and -9 in the forming zone of rat incisor. Light microscope immunohistochemistry carried out on undemineralized material provided evidence for strong MMP-2 staining in the secretory ameloblasts, odontoblasts, in the enamel organ, and in the pulp. A weaker staining was observed in predentin and in the outer part of the forming enamel. Using MMP-9 antibodies, the staining was generally weak, except for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…At the light microscope level, few studies have reported the distribution of these SLRPs during tooth development, although their distribution has been extensively examined using iEM. The patterns observed in the current light microscopy study resemble those demonstrated by Goldberg and co-workers [26] in the mouse first molar at post-natal day one. However, their study demonstrated significant levels of BGN, DCN and FMD in the developing enamel organ, which differs from the present study.…”
Section: Discussionsupporting
confidence: 88%
“…At the light microscope level, few studies have reported the distribution of these SLRPs during tooth development, although their distribution has been extensively examined using iEM. The patterns observed in the current light microscopy study resemble those demonstrated by Goldberg and co-workers [26] in the mouse first molar at post-natal day one. However, their study demonstrated significant levels of BGN, DCN and FMD in the developing enamel organ, which differs from the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Several MMPs have been identified in dentin and pulp (Boukpessi et al , 2008, Goldberg et al, 2003, Palosaari et al , 2003) and are thought to be implicated in the early stages of dentinogenesis. Among endogenous MMPs, MMP-2 has been proposed to be involved in dental ECM processing taking place at later stages of tooth development, and particularly in dentin sialophosphoprotein (DSPP) processing, possibly in association with MMP-20 (Bourd-Boittin et al , 2005, Yamakoshi et al , 2006), or in association with a self-processing mechanism of DSPP (Godovikova and Ritchie, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the presence of several proteinases in the enamel space to degrade EMPs3456, the transporting mechanisms of EMP debris across ameloblasts are of equal importance in ensuring enamel health. Earlier understanding of cellular uptake of EMPs from enamel space seems to favor a passive diffusion or non-specific internalization pattern1213141516.…”
Section: Discussionmentioning
confidence: 99%
“…Ameloblasts in secretory stage mainly function to synthesize and secrete a series of enamel matrix proteins (EMPs) into the future enamel space2. During enamel maturation, EMPs are fragmented extracellularly in the presence of ameloblast-derived proteinases3456. The EMP debris is retrieved by ameloblasts for further degradation within the cellular endosomal/lysosomal apparatus789, and the concomitant ion flux through the ameloblasts gives rise to mature tooth enamel with highly organized crystal structure.…”
mentioning
confidence: 99%